Implementation of Life Cycle Costing on Airline Industry (Case Study of XYZ Airline in Indonesia) - Winten Adnyano , Wayan; Abdul Chalid, Dony (KnE Social Sciences, 2020)
The airline operating cost may vary along the operation time of the aircraft. This cost fluctuation should be taken as consideration for the decision-making process, for instance, the pricing calculation. A poor costing might distort pricing leading to a loss of business. A long-term oriented cost calculation to forecast the total cost of aircraft during the operation time is critical for the airline company. This research will study whether the life cycle cost analysis is fit for airline company with an emphasis on maintenance and disposal or aircraft redelivery cost and focus on aircraft operating lease context. It uses a case study framework on an airline in Indonesia with the interview and documentation analysis as the main research method. The life cycle cost is found to be fit for the airline company with activity-based life-cycle costing as the applicative model. The research presents an approach that provides a long-term oriented costing that is needed for management decision. Keywords: life cycle costing, airline operating cost